Sebaran dan Persentase Serangan Hama Paralecta sp. Pada Tanaman Cengkeh di Kabupaten Kepulauan Sangihe - Yunita Tahulending; Jackson F. Watung; Bernadeth V. Montong; Sandra E. Pakasi (Universitas Sam Ratulangi, 2020)
ABSTRACTClove (Syzygium aromaticum L) is a trade plant that has a high economic value in Indonesia.This study aims to determine the distribution and percentage of pest attacks Paralecta sp. inthe Sangihe Islands Regency. This study uses a survey method or direct research at theresearch location. The study was conducted at several clove plantation locations in theSangihe Islands. Observation of the distribution of branch borer pests and clove branches wascarried out in clove plantations, then marked using GPS and recorded coordinate points thencopied to map images using the arcMap 10.5 mapping program. Observation The percentageof attacks carried out on plantations used as sample locations and determined 25 sample treesto be used to calculate the percentage of attacks. Results of the study There were 18 locationsfound pests attack Paralecta sp. namely in the Central Sangihe and to the southern part withthe percentage of attacks that reached 100%, namely in the Village of Malamenggu 448meters above sea level, 435 meters above sea level and 8 points of location that were notfound is a pest attack Paralecta sp. that is, in the middle of Sangihe to the northern part ofSangihe with 0% attack percentage.Keywords: Clove, Distribution, Paralecta sp. Percentage of attack